Homeschooling and financial literacy: a qualitative analysis - Henegar, Justin M. (Kansas State University, 2014)
Financial literacy has become a prominent topic of discussion since the latest economic downturn. Although many studies reveal that our youth’s financial literacy is low, no study to date provides an overview as to how our youth are learning financial literacy concepts. This dissertation seeks to explore how homeschooling families prepare their children to be financially literate. This study reviewed four sensitizing concepts: (a) communication, (b) engagement, (c) outside influences, and (d) parental perspectives based on the learning theory: Legitimate Peripheral Participation. Twenty primary educators in homeschooling families from a variety of states were interviewed for this study. Out of the twenty participants, eight were classified in the elementary age group, five were classified in the middle school age, and seven were classified in the high school age. Each sensitizing concept was examined for each school age group. This exploratory study found that parents who homeschool tend to focus on three main topics of personal finance: debt or the avoidance of debt, savings, and budgeting. Little evidence suggests that parents help their children with the mechanics of these behaviors. There were three important findings extracted in this study. First, the results suggest that homeschooling parents need to become better prepared to teach their children about money, and second, that personal finance should be thought of as a core subject in the elementary age years in lieu of just a life skill. Finally, this study found that there is a large focus around personal finance topics in the elementary age years and the high school years, with little attention to personal finance behaviors for the middle school age group. The results of this study provide those entities that advocate improved financial literacy an understanding as to the “how” parents who homeschool prepare their kids to understand money.
Keywords: Financial literacy; Homeschooling; Financial education; Individual & Family Studies (0628)